Vestibular evoked myogenic potentials: an overview - Cal,Renato (2009)
The vestibular evoked myogenic potential (VEMP) test is a relatively new diagnostic tool that is in the process of being investigated in patients with specific vestibular disorders. Briefly, the VEMP is a biphasic response elicited by loud clicks or tone bursts recorded from the tonically contracted sternocleidomastoid muscle, being the only resource available to assess the function of the saccule and the lower portion of the vestibular nerve. AIM: In this review, we shall highlight the history, methods, current VEMP status, and discuss its specific application in the diagnosis of the Ménière's Syndrome.